Cytogenetics of Festulolium (Festuca x Lolium hybrids) - Kopecký, D; Lukaszewski, A J; Dolezel, J (Cytogenetic and genome research, 2008)
Grasses are the most important and widely cultivated crops. Among them, ryegrasses (Lolium spp.) and fescues (Festuca spp.) provide high quality fodder for livestock, are used for turf and amenity purposes, and play a fundamental role in environment protection. Species from the two genera display complementary agronomic characteristics and are often grown in mixtures. Breeding efforts to combine desired features in single entities culminated with the production of Festuca x Lolium hybrids. The so called Festuloliums enjoy a considerable commercial success with numerous cultivars registered all over the world. They are also very intriguing from a strictly cytogenetic point of view as the parental chromosomes recombine freely in hybrids. Until a decade ago this phenomenon was only known in general quantitative terms. The introduction of molecular cytogenetic tools such as FISH and GISH permitted detailed studies of intergeneric chromosome recombination and karyotyping of Festulolium cultivars. These tools were also invaluable in revealing the origin of polyploid fescues, and facilitated the development of chromosome substitution and introgression lines and physical mapping of traits of interest. Further progress in this area will require the development of a larger set of cytogenetic markers and high-resolution cytogenetic maps. It is expected that the Lolium-Festuca complex will continue providing opportunities for breeding superior grass cultivars and the complex will remain an attractive platform for fundamental research of the early steps of hybrid speciation and interaction of parental genomes, as well as the processes of chromosome pairing, elimination and recombination.
Keywords: cytogenetika; Breeding; Hybridization, Genetic; Chromosomes, Plant; Physical Chromosome Mapping; In Situ Hybridization, Fluorescence; Festuca; chov; Meiosis; hybridizace genetická; Genome, Plant; molekulární biologie; Lolium; Cytogenetics; meióza; Ploidies; ploidie; hybridizace in situ fluorescenční; jílek; chromozomy rostlin; Molecular Biology; genom rostlinný; fyzikální mapování chromozomů